Ethical issues related to the use of gerontechnology in older people care: A scoping review - Sundgren, Suvi (Nursing ethics, 2020)
Background:Demographic trends indicate growth of population aged 65 and older in Western countries. One of the greatest challenges is to provide high-quality care for all. Technological solutions designed for older people, gerontechnology, can somewhat balance the gap between resources and the increasing demand of healthcare services. However, there are also ethical issues in the use of gerontechnology that need to be pointed out.Purpose:To describe what ethical issues are related to the use of gerontechnology in the care of community-dwelling older people.Methods:A scoping review was performed to identify and analyse studies concerning ethical issues when using gerontechnology in the home care of older people. The literature search was limited to studies published after 1990 and addressed to the electronic databases CINAHL, PubMed, Cochrane, Medic, IEEE Explore and Web of Science. The search was performed in July−August 2018. Data from empirical studies were analysed using thematic analysis.Ethical considerations:This scoping review was conducted in accordance with good scientific practice. The work of other researchers was respected and cited appropriately.Results:A total of 17 studies were identified. Two main themes were found. ‘Balancing between the benefits of using gerontechnology and the basic rights of older people’, consisted of the subthemes safety, privacy and autonomy. The other main theme, ‘Gerontechnology as a risk of insecurity for older people’, included the subthemes fear of losing human contact and concern and fear. Surveillance and monitoring technologies were mainly studied.Conclusion:These results suggest that there may be ethical issues related to the use of gerontechnology and they must therefore be taken into consideration when implementing technology in the care of community-dwelling older people.